Molecular subtype and response to dasatinib, an Src/Abl small molecule kinase inhibitor, in hepatocellular carcinoma cell lines in vitro. Issue 5 (1st April 2013) - Finn, Richard S.; Aleshin, Alexey; Dering, Judy; Yang, Peter; Ginther, Charles; Desai, Amrita; Zhao, Danyun; von Euw, Erika; Busuttil, Ronald W.; Slamon, Dennis J.
Abstract: Hepatocellular carcinoma (HCC) is the fifth most common malignancy and is the third leading cause of cancer death worldwide. Recently, the multitargeted kinase inhibitor sorafenib was shown to be the first systemic agent to improve survival in advanced HCC. Unlike other malignancies such as breast cancer, in which molecular subtypes have been clearly defined (i.e., luminal, HER2 amplified, basal, etc.) and tied to effective molecular therapeutics (hormone blockade and trastuzumab, respectively), in HCC this translational link does not exist. Molecular profiling studies of human HCC have identified unique molecular subtypes of the disease. We hypothesized that a panel of human HCC cell lines would maintain molecular characteristics of the clinical disease and could then be used as a model for novel therapeutics. Twenty human HCC cell lines were collected and RNA was analyzed using the Agilent microarray platform. Profiles from the cell lines in vitro recapitulate previously described subgroups from clinical material. Next, we evaluated whether molecular subgroup would have predictive value for response to the Src/Abl inhibitor dasatinib. The results demonstrate that sensitivity to dasatinib was associated with a progenitor subtype. Dasatinib was effective at inducing cell cycle arrest and apoptosis in "progenitor‐like" cell lines but not in resistant lines. Conclusion: These findings suggest that cell line models maintain the molecular background of HCC and that subtype may be important for selecting patients for response to novel therapies. In addition, it highlights a potential role for Src family signaling in this progenitor subtype of HCC. (HEPATOLOGY 2013)